Risk management under impacts of macro economic factors in a big seafood Ex-Import Firm - AnGiang Fisheries Ex-Import jsc. in Vietnam - Thach Nguyen Ngoc; Huy Dinh Tran Ngoc (Zielona Góra: Faculty of Economics and Management Press)
AnGiang Fisheries Ex-Import Joint Stock Company (AGF) was established in 2001. Agifish has traditionally been a leader in the fields of production and business activities, scientific research in the field of fingerling production, seafood processing technology and the development of value added products processed from Basa-fish, Tra-fish. Agifish cares about building a spirit of solidarity between leaders, managers and workers striving for the development of the Company.
Keywords: risk management; macroeconomic factors; Vietnam; AGF stock price; GDP growth; inflationary; risk free rate; market interest rate; zarządzanie ryzykiem; czynniki makroekonomiczne; Wietnam; akcje AGF; wzrost PKB; inflacja; rynkowa stopa procentowa